Polyimide fiber sizing agent for synergistic repair sizing as well as preparation method and application of polyimide fiber sizing agent
By using a sizing agent of multifunctional epoxy resin and a low boiling point solvent, the internal structural defects of high-performance polyimide fibers and the surface chemical activity are coordinated to solve the problems of fiber mechanical properties and application breadth, and the improvement of fiber performance and process cost are achieved.
Patent Information
- Application Number
- CN202411881764.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
High-performance polyimide fibers have structural defects and surface inertia inside the fiber, limiting their mechanical properties and the breadth of composite materials applications.
The sizing agent is used with a multifunctional epoxy resin and a low-boiling solvent acetone or ethanol as raw materials to jointly repair the internal structural defects of the fiber and improve the chemical activity of the fiber surface through impregnation treatment.
The tensile strength, compression strength and interface shear strength of the fiber are significantly improved, while reducing process costs and waste liquid recycling difficulty.
Smart Images

Figure CN119686118A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance organic fibers, and in particular to a polyimide fiber sizing agent and a preparation method and application thereof. Background Art
[0002] High-performance organic fibers are widely used in aerospace, electronic power, safety protection and other fields due to their excellent properties such as high strength, high modulus, light weight, high temperature resistance and chemical resistance. In the process of fiber preparation, due to the characteristics of its spinning process, structural defects are inevitably formed inside the fiber, which affects the further improvement of mechanical properties such as tensile strength and compressive strength. At the same time, the fiber surface is smooth, the chemical activity is low, the adhesion with the matrix material is poor, and the surface is chemically inert, which limits its application in the field of composite materials.
[0003] In response to the problem of internal structural defects in fibers, many scholars have adopted structural design methods to reduce the generation of internal defects in fibers by enhancing radial interactions between molecules, but this method has high trial and error costs and is time-consuming. In terms of improving fiber surface properties, the sizing method is widely used because of its simple process and easy industrial production. It can form a covering layer on the fiber surface and improve the surface activity of the fiber through the active functional groups in the sizing agent. The solvent of the mainstream sizing agent is water, and the solute is an aqueous monomer, such as water-based epoxy, water-based polyurethane, silane coupling agent, etc. Currently, public literature reports show that the use of water-based sizing agents can effectively improve the inertness of the fiber surface, but its repair effect on microporous defects inside the fiber has not yet been found. Liu Xiangyang et al. used high-boiling-point DMAc as solvent and methyl methacrylate / benzoyl peroxide / divinylbenzene cross-linking component as solute to treat aramid fiber, achieving internal fiber repair and surface roughness improvement, thereby improving interfacial shear strength and single fiber compression performance (Lv, J.; Yin, J.; Qin, Y.; Dai, Y.; Cheng, Z.; Luo, L.; Liu, X., Post-construction of weaving structure in aramid fiber towards improvements of its transverse properties. Composites Science and Technology 2021, 208.). This method has a complex cross-linking system and uses a high-boiling-point solvent, and the waste liquid is not easy to recycle. At the same time, the improvement of the interfacial bonding strength between the fiber and the resin mainly relies on mechanical meshing, there is no chemical reaction, and the bonding force is relatively weak. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a simple polyimide fiber sizing agent, which can synergistically repair sizing, that is, synergistically repair internal structural defects of high-performance polyimide fibers and improve the chemical activity of the fiber surface, and the waste liquid is easy to recycle and the cost is low.
[0005] Another object of the present invention is to provide a method for preparing the polyimide fiber sizing agent.
[0006] Another object of the present invention is to provide a sizing method using the above-mentioned polyimide fiber sizing agent.
[0007] Another object of the present invention is to provide an application of the polyimide fiber sizing agent or the sizing method.
[0008] According to the purpose of the present invention, the present invention provides a polyimide fiber sizing agent, the raw materials of which are composed of solute A and solvent B, the solute A is a multifunctional epoxy resin, the solvent B is a low boiling point solvent, the low boiling point solvent is acetone or ethanol, and the ratio of the solute A to the solvent B is as follows by weight percentage:
[0009] A 0.1%~10%
[0010] B 90%~99.9%.
[0011] The polyimide fiber sizing agent of the present invention can be used to synergistically repair the internal structural defects of high-performance polyimide fibers and improve the chemical activity of the fiber surface. It can improve the fiber surface roughness and surface chemical reactivity in a relatively short time, and at the same time repair the internal defects of the fiber through the formation of internal crosslinking points. The tensile strength and compressive strength of the fiber are both improved. The system is simple, the waste liquid is easy to recycle, and the cost is low.
[0012] Solute A is a multifunctional epoxy resin, preferably with a functionality of 3 to 4. A multifunctional epoxy resin with a functionality of 3 is, for example, triglycidyl p-aminophenol, and a multifunctional epoxy resin with a functionality of 4 is, for example, tetraglycidyl-4,4'-diaminodiphenylmethane. The structural formulas are respectively as follows:
[0013]
[0014] For example, in a preferred embodiment, the solute A is AG-80 epoxy resin, which is an industrially produced tetraglycidyl-4,4'-diaminodiphenylmethane, and the solvent B is acetone.
[0015] Preferably, the ratio of the solute A to the solvent B is:
[0016] A 1%~7%
[0017] B 93%~99%.
[0018] In the above ratios, solute A can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, or 7%, and solvent B can be, for example, 93%, 94%, 95%, 96%, 97%, 98%, or 99%. The percentages of solute A and solvent B must be selected so that their sum is 100%.
[0019] According to another object of the present invention, the present invention provides a method for preparing a polyimide fiber sizing agent, which comprises the following steps: dissolving the epoxy resin in the low boiling point solvent, mixing uniformly, and preparing the polyimide fiber sizing agent.
[0020] According to another object of the present invention, the present invention provides a sizing method, which uses the above-mentioned polyimide fiber sizing agent to size organic fibers. The sizing method of the present invention can be applied to a variety of organic fibers, including polyimide fibers, aramid fibers, poly(p-phenylene benzobisoxazole) (PBO) fibers, etc.
[0021] Preferably, the organic fiber is one or more selected from polyimide fiber, aramid fiber, poly(p-phenylene benzobisoxazole) fiber.
[0022] Preferably, when the organic fiber is polyimide fiber, the sizing method comprises the following steps:
[0023] 1) Immersing and repairing sizing: immersing the polyimide fiber in the polyimide fiber sizing agent at a temperature of 10° C. to 45° C. for 1 min to 24 h, and then taking out the polyimide fiber;
[0024] 2) Removing the residual solution: drying the taken-out polyimide fiber at a temperature of 50° C. to 110° C. for 2 to 60 minutes to obtain sized polyimide fiber.
[0025] The soaking time in the above step 1) is preferably 2 min to 10 min.
[0026] According to the above purpose, the present invention also provides a sized polyimide fiber, which is a sized polyimide fiber prepared by the sizing method according to claim 6, wherein the tensile strength of the single filament is increased by more than 4% compared with the unsized fiber, the compressive strength of the multifilament is increased by more than 37% compared with the unsized fiber, and the interface shear strength is increased by more than 40% compared with the unsized fiber. Furthermore, compared with the unsized polyimide fiber, the tensile strength of the single filament is increased by 4% to 20%, the compressive strength of the multifilament is increased by 37% to 60%, and the interface shear strength is increased by 40% to 80%.
[0027] According to another object of the present invention, the present invention provides use of the above-mentioned polyimide sizing agent, sizing method or sized polyimide fiber in preparing a composite material.
[0028] In the application of the present invention, the composite material may be a polyimide fiber reinforced composite material used in the fields of aerospace, safety protection, electronic power, automobiles, sports equipment, sporting goods, etc.
[0029] High-performance organic fibers, molecular chains radially rely on weak interaction forces to combine, coupled with the double diffusion effect during actual spinning coagulation, the original fibers (inside the fiber) will inevitably produce micropores and skin-core structures, and the fiber surface is inert, which is not conducive to the interface bonding between the fiber and the resin. At present, with regard to internal defects of the fiber, the mainstream adopts molecular structure design or the method of adjusting the spinning process to improve, the trial and error cost is high, and the industrialization cycle is long; with regard to fiber surface activation, the sizing method is a commonly used method for fiber surface modification in industry, and water-based sizing agents are mostly used, but the contact angle between water and fiber is large. The present invention is based on polar low-viscosity organic solvents, which greatly reduces the contact angle between the fiber and the solution, improves the contact wettability of the solution, helps to penetrate epoxy monomers, enables multifunctional epoxy to become the internal crosslinking point of the fiber, and repairs the pores between the original fibers. The epoxy monomers remaining on the surface further improve the surface roughness and chemical reactivity, efficiently improve the fiber surface interface performance, and improve the internal fiber structural defects and surface inertia.
[0030] Therefore, the present invention improves both the internal and surface problems of the fiber, and greatly saves the cost of fiber structure and process design by the way of impregnation sizing treatment. The present invention can not only improve the surface activity of the fiber, including all the advantages of sizing treatment, but also repair the inside of the fiber, and improve the tensile strength of the fiber and the compressive strength of the multifilament.
[0031] In addition, acetone or ethanol is used as a low boiling point solvent in the present invention, which has high polarity and ultra-low viscosity. The solvent has very good contact and wetting properties with the fiber, so it can help small molecules enter the fiber interior, and take into account the surface sizing modification. While the surface roughness increases, the epoxy monomer also ensures the surface chemical reactivity. In addition, after sizing modification, due to the low boiling point of the solvent, the solution components are not complicated, so recycling can also solve the waste liquid problem and reuse it, reducing costs.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The sizing agent of the present invention can simultaneously repair the internal defects of the fiber and improve the surface activity, and the sizing treatment by immersion greatly saves the cost of fiber structure and process design;
[0034] (2) The sizing agent uses a low-boiling point solvent, the solution components are simple, and the waste liquid is easy to recycle and reuse, reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope photograph of the torn surface of the polyimide fiber after repair and sizing in Example 1.
[0036] Figure 2 This is a scanning electron microscope photograph of the tear surface of the unsized polyimide fiber of Comparative Example 1.
[0037] Figure 3 This is a scanning electron microscope photograph of the adhesion between the polyimide fiber monofilaments of Comparative Example 4. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. If the specific conditions are not specified in the examples, they shall be carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The polyimide fiber filaments used in the experiment were provided by Jiangsu Xiannuo; the aramid fiber was aramid 1414 fiber purchased from Yantai Taihe New Materials Co., Ltd., and the PBO fiber was purchased from Zhonglan Chenguang Chemical Research and Design Institute Co., Ltd. The multifunctional epoxy resin AG-80 used is an industrially produced tetraglycidyl-4,4'-diaminodiphenylmethane, and the multifunctional epoxy resin AFG-90 is an industrially produced triglycidyl p-aminophenol.
[0039] Parameter determination method:
[0040] Single filament tensile strength: The single filament tensile breaking strength of the fiber is tested in accordance with GB / T 31290-2022 "Determination of tensile properties of carbon fiber single filaments".
[0041] Multifilament compressive strength: The multifilament compressive strength is tested in accordance with Q / 110000BH005-2018 "Test method for compressive strain and compressive strength of carbon fiber multifilament".
[0042] Interface shear strength: tested by composite material interface performance evaluation instrument (HM410), the microspheres are cured by epoxy resin E51 and D400, and the diameter of the microspheres is 50-80um;
[0043] Fiber micromorphology: The fiber was characterized by scanning electron microscopy (JSM-7800F).
[0044] Example 1
[0045] Solute component A: multifunctional epoxy resin AG-80
[0046] Solvent B component: acetone
[0047] Ratio of solute A to solvent B (by weight percentage):
[0048] A 4%
[0049] B 96%
[0050] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0051] Sizing modification method:
[0052] (1) immersing the polyimide fiber in the synergistic repair sizing solution at 25° C. for 2 minutes, and then taking out the fiber;
[0053] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing polyimide fibers;
[0054] The test shows that the tensile strength of the polyimide fiber monofilament is 4232MPa, which is 10% higher than that of the unrepaired sizing fiber. The compressive strength of the multifilament is 278.1MPa, which is 53% higher than that of the unrepaired sizing fiber. The interfacial shear strength is 38.07MPa, which is 73% higher than that of the unrepaired sizing fiber.
[0055] In addition, the microscopic morphology of the torn surface of the repaired polyimide fiber after sizing in Example 1 was characterized by a scanning electron microscope (JSM-7800F). Figure 1 .Depend on Figure 1 As shown, after repair sizing, the internal defects of the fiber are repaired.
[0056] Example 2
[0057] Solute component A: multifunctional epoxy resin AG-80
[0058] Solvent B component: acetone
[0059] Ratio of solute A to solvent B (by weight percentage):
[0060] A 0.1%
[0061] B 99.9%
[0062] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0063] Sizing modification method:
[0064] (1) immersing the polyimide fiber in the synergistic repair sizing solution at 25° C. for 24 hours, and then taking out the fiber;
[0065] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing aramid fibers;
[0066] The test results show that the tensile strength of the single filament is 4198MPa, which is 9% higher than that of the unrepaired sizing fiber. The compressive strength of the multifilament is 256.8MPa, which is 42% higher than that of the unrepaired sizing fiber. The interfacial shear strength is 35.80MPa, which is 63% higher than that of the unrepaired sizing fiber. In addition, the scanning electron microscope photos of the fiber tear surface are similar to Figure 1 Similarly, it was shown that the internal defects of the fibers were repaired after repair sizing.
[0067] Example 3
[0068] Solute component A: multifunctional epoxy resin AFG-90
[0069] Solvent B component: acetone
[0070] Ratio of solute A to solvent B (by weight percentage):
[0071] A 10%
[0072] B 90%
[0073] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0074] Sizing modification method:
[0075] (1) The polyimide fiber is immersed in the synergistic repair sizing solution at 25° C. for 1 minute, and then the fiber is taken out;
[0076] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing polyimide fibers;
[0077] The test results show that the tensile strength of the single filament is 3987MPa, which is 4% higher than that of the unrepaired sizing fiber. The compressive strength of the multifilament is 253.3MPa, which is 40% higher than that of the unrepaired sizing fiber. The interfacial shear strength is 31.20MPa, which is 42% higher than that of the unrepaired sizing fiber. In addition, the scanning electron microscope photos of the fiber tear surface are similar to Figure 1 Similarly, it was shown that the internal defects of the fibers were repaired after repair sizing.
[0078] Example 4
[0079] Solute component A: multifunctional epoxy resin AG-80
[0080] Solvent B component: ethanol
[0081] Ratio of solute A to solvent B (by weight percentage):
[0082] A 2%
[0083] B 98%
[0084] Preparation method: dissolve epoxy monomer A in solvent ethanol, mix well, and obtain a synergistic repair sizing solution.
[0085] Sizing modification method:
[0086] (1) immersing the polyimide fiber in the synergistic repair sizing solution at 25° C. for 10 hours, and then taking out the fiber;
[0087] (2) drying the removed fibers at 50° C. for 30 min to obtain repaired and sized polyimide fibers;
[0088] The test results show that the tensile strength of the single filament is 4058MPa, which is 6% higher than that of the unrepaired sizing fiber. The compressive strength of the multifilament is 248.9MPa, which is 37% higher than that of the unrepaired sizing fiber. The interfacial shear strength is 30.82MPa, which is 40% higher than that of the unrepaired sizing fiber. In addition, the scanning electron microscope photos of the fiber tear surface are similar to Figure 1 Similarly, it was shown that the internal defects of the fibers were repaired after repair sizing.
[0089] Example 5
[0090] Solute component A: multifunctional epoxy resin AG-80
[0091] Solvent B component: acetone
[0092] Ratio of solute A to solvent B (by weight percentage):
[0093] A 4%
[0094] B 96%
[0095] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0096] Sizing modification method:
[0097] (1) immersing the aramid fiber in the synergistic repair sizing solution at 25° C. for 2 minutes, and then taking out the fiber;
[0098] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing aramid fibers;
[0099] After testing, the tensile strength of the single fiber is 3608MPa, which is 14% higher than that of the unrepaired sizing fiber. The compressive strength of the multifilament is 235.8MPa, which is 44% higher than that of the unrepaired sizing fiber. The interfacial shear strength is 36.94MPa, which is 63% higher than that of the unrepaired sizing fiber. In addition, the scanning electron microscope photos of the tear surface of the unsized aramid fiber are similar to Figure 2 Similarly, the SEM images of the torn surface of the aramid fiber after repair and sizing are similar to Figure 1 Similarly, it is shown that the unsized aramid fibers have internal defects, whereas after repair sizing, the internal defects of the fibers are repaired.
[0100] Example 6
[0101] Solute component A: multifunctional epoxy resin AG-80
[0102] Solvent B component: acetone
[0103] Ratio of solute A to solvent B (by weight percentage):
[0104] A 4%
[0105] B 96%
[0106] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0107] Sizing modification method:
[0108] (1) The PBO fiber is immersed in the synergistic repair sizing solution at 25°C for 2 minutes, and then the fiber is taken out;
[0109] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired and sized PBO fibers;
[0110] The test results show that the tensile strength of the single filament is 6076MPa, which is 6% higher than that of the unrepaired sized fiber. The compressive strength of the multifilament is 229.8MPa, which is 39% higher than that of the unrepaired sized fiber. The interfacial shear strength is 30.76MPa, which is 48% higher than that of the unrepaired sized fiber. In addition, the scanning electron microscope photos of the tear surface of the unsized PBO fiber are similar to Figure 2 Similarly, the SEM images of the torn surface of PBO fibers after repair and sizing are similar to Figure 1 Similarly, it was shown that the unsized PBO fibers had internal defects, whereas after repair sizing, the internal defects of the fibers were repaired.
[0111] Comparative Example 1
[0112] For the unsized polyimide fiber, it was measured that the tensile strength of the polyimide fiber original fiber was 3852 MPa, the compressive strength of the multifilament was 181.2 MPa, and the interfacial shear strength was 22.01 MPa.
[0113] In addition, the microscopic morphology of the tear surface of the unsized polyimide fiber of Comparative Example 1 was characterized by scanning electron microscopy (JSM-7800F). Figure 2 .Depend on Figure 2 As shown, the unsized fibers have internal defects.
[0114] Comparative Example 2
[0115] The unsized aramid fiber was tested to have a single-filament tensile strength of 3165 MPa, a multifilament compressive strength of 163.2 MPa, and an interfacial shear strength of 22.67 MPa. In addition, the microscopic morphology of the tear surface of the unsized aramid fiber of Comparative Example 2 was characterized using a scanning electron microscope (JSM-7800F). Figure 2 Similarly, the unsized fibers were shown to have internal defects.
[0116] Comparative Example 3
[0117] The unsized PBO fiber was tested to have a single-filament tensile strength of 5730 MPa, a multifilament compressive strength of 165.90 MPa, and an interfacial shear strength of 20.78 MPa. In addition, the microscopic morphology of the tear surface of the unsized PBO fiber of Comparative Example 3 was characterized using a scanning electron microscope (JSM-7800F). The scanning electron microscope photographs were similar to those of Figure 2 Similarly, the unsized fibers were shown to have internal defects.
[0118] Comparative Example 4
[0119] Solute component A: multifunctional epoxy resin AG-80
[0120] Solvent B component: acetone
[0121] Ratio of solute A to solvent B (by weight percentage):
[0122] A 0.05%
[0123] B 99.95%
[0124] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0125] Sizing modification method:
[0126] (1) immersing the polyimide fiber in the synergistic repair sizing solution at 25° C. for 24 hours, and then taking out the fiber;
[0127] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing polyimide fibers;
[0128] After testing, the fiber single filament tensile strength is 3690MPa, which is 4% lower than that of unrepaired sizing fiber. The multifilament compression strength is 176.7MPa, which is 2% lower than that of unrepaired sizing fiber. The interfacial shear strength is 20.50MPa, which is 7% lower than that of unrepaired sizing fiber.
[0129] Comparative Example 5
[0130] Solute component A: multifunctional epoxy resin AG-80
[0131] Solvent B component: acetone
[0132] Ratio of solute A to solvent B (by weight percentage):
[0133] A 15%
[0134] B 85%
[0135] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0136] Sizing modification method:
[0137] (1) The polyimide fiber is immersed in the synergistic repair sizing solution at 25° C. for 1 minute, and then the fiber is taken out;
[0138] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing polyimide fibers;
[0139] After testing, it was found that adhesion occurred between the fiber filaments. Figure 3 This is a scanning electron microscope photograph of the adhesion between the polyimide fiber monofilaments of Comparative Example 4.
[0140] Comparative Example 6
[0141] Solute component A: multifunctional epoxy resin AG-80
[0142] Solvent B component: acetone
[0143] Ratio of solute A to solvent B (by weight percentage):
[0144] A 10%
[0145] B 90%
[0146] Preparation method: dissolve epoxy monomer A in solvent acetone, mix well, and obtain a synergistic repair sizing solution.
[0147] Sizing modification method:
[0148] (1) The polyimide fiber is immersed in the synergistic repair sizing solution at 25° C. for 30 seconds, and then the fiber is taken out;
[0149] (2) drying the removed fibers at 70° C. for 30 min to obtain repaired sizing polyimide fibers;
[0150] After testing, the fiber single filament tensile strength is 3896MPa, which is only 1% higher than that of unrepaired sizing fiber. The multifilament compression strength is 185.8MPa, which is only 3% higher than that of unrepaired sizing fiber. The interfacial shear strength is 23.87MPa, which is only 8% higher than that of unrepaired sizing fiber.
[0151] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A polyimide fiber sizing agent, characterized in that: The raw materials of the polyimide fiber sizing agent are composed of solute A and solvent B, wherein the solute A is a multifunctional epoxy resin, and the solvent B is a low boiling point solvent, wherein the low boiling point solvent is acetone or ethanol, and the ratio of the solute A to the solvent B is as follows: A 0.1%~10% B 90%~99.9%。 2. The polyimide fiber sizing agent according to claim 1, characterized in that: The functionality of the multifunctional epoxy resin is 3-4.
3. The polyimide fiber sizing agent according to claim 1 or 2, characterized in that: The ratio of the solute A to the solvent B is: A 1%~7% B 93%~99%。 4. The polyimide fiber sizing agent according to claim 2, characterized in that: The multifunctional epoxy resin is triglycidyl p-aminophenol or tetraglycidyl-4,4'-diaminodiphenylmethane.
5. The method for preparing a polyimide fiber sizing agent according to any one of claims 1 to 4, characterized in that: The following steps are involved: The multifunctional epoxy resin is dissolved in the low boiling point solvent and mixed evenly to prepare a polyimide fiber sizing agent.
6. A sizing method, characterized in that: The polyimide fiber sizing agent according to any one of claims 1 to 4 is used to sizing organic fibers.
7. The sizing method according to claim 6, characterized in that: The organic fiber is one or more selected from polyimide fiber, aramid fiber, poly(p-phenylene benzobisoxazole) fiber; and / or When the organic fiber is polyimide fiber, the sizing method comprises the following steps: 1) Immersing and repairing sizing: immersing the polyimide fiber in the polyimide fiber sizing agent at a temperature of 10° C. to 45° C. for 1 min to 24 h, and then taking out the polyimide fiber; 2) Removing the residual solution: drying the taken-out polyimide fiber at a temperature of 50° C. to 110° C. for 2 min to 60 min to obtain sized polyimide fiber.
8. The sizing method according to claim 6, characterized in that: In step 1), soak for 2 to 10 minutes.
9. A sizing polyimide fiber, characterized in that: The sized polyimide fiber is prepared by the sizing method according to claim 7 or 8. Compared with the unsized polyimide fiber, the tensile strength of the single yarn is increased by 4% to 20%, the compressive strength of the multifilament is increased by 37% to 60%, and the interface shear strength is increased by 40% to 80%.
10. Use of the polyimide fiber sizing agent according to any one of claims 1 to 4, the sizing method according to any one of claims 6 to 8, or the sized polyimide fiber according to claim 9 in preparing a composite material, The composite material is a polyimide fiber reinforced composite material in the fields of aerospace, safety protection, electronic power, automobile, sports equipment, or sporting goods.
Citation Information
Patent Citations
Sizing agent-coated reinforcing fibers, method for producing sizing agent-coated reinforcing fibers, prepreg, and fiber-reinforced composite material
CN106068346A
Graphene oxide-containing poly-functional group epoxy resin-based water-soluble sizing agent and preparation method thereof
CN107385921A
Sizing process of polyimide fibers
CN110295494A
High-temperature-resistant water-soluble sizing agent, modified carbon fiber and reinforced polymer-based composite material thereof
CN118621588A
Sizing agent for carbon fiber
JP1993051871A